Cytotoxicity Effect of Arnebia Euchroma against Human Gastric - Mohammad-Reza; Mehrdad Karimi; Noor Fattah; Mohammad Tahvil-zade; Saeed Nazarbeigi (Tehran University of Medical Sciences, 2016)
Introduction: Despite the reduction in the incidence of gastric cancer during the past 75 years, it remains the most common cause of death from cancer in Iran and now despite all the progress made, the 5-year survival of patients is generally 15%. Thus, improvement in current treatments seems necessary. Given the richness of Iranian medicine in ancient texts, a detailed study of the effects of medicinal plants native to Iran in particular is essential. In this research, the cytotoxicity effect of Arnebia euchoromaon AGS was reviewed. Materials and Methods: In this study, cells were cultured in RPMI at different concentrations of Arnebia euchoroma extract (5,2,1,0.2,0.1,0.05 and 0.02 mg/ml) at intervals of 24,48 and 72 h and the number of living cells compared with the control group and cytotoxicity effect were measured by MTT assay. Results:Within 24 hours, drug effects on reduction of cell growth of AGS in comparison to the control group at 5, 1, 0.1, 0.05 and 0.02 mg/ml were significant (P values are 0.0305, 0.0465, 0.0137, 0.0274and 0.0003, respectively). Within 48 hours, concentrations of 0.1 and 0.02 mg/ml were significant (P values are 0.0398 and 0.0143).Within 72 hours, 5, 0.05 and 0.02 mg/ml reductions were significant (P values are 0.0402, 0.0073 and 0.0349, respectively). Conclusion: According to the results, Arnebia euchoroma significantly has no killing effect on AGS.Only in the 0.02 mg/ml concentrations the reduction was significant at three times, with a fatality rate of about 20%, which is not enough to be considered cytotoxic.